2019
DOI: 10.1136/bmjopen-2019-030158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed diabetes mellitus and associated factors among adult residents of Bahir Dar city, northwest Ethiopia: a community-based cross-sectional study

Abstract: ObjectiveTo assess the prevalence of undiagnosed diabetes mellitus (DM) and associated factors among adult inhabitants of Bahir Dar city, northwest Ethiopia.DesignA community-based cross-sectional study was conducted on adults (n=607) of Bahir Dar city from 10 March to 20 May 2018.MeasurementsData were collected using structured interviewer-administered questionnaire, and anthropometric measurements were taken from each participant. Fasting blood sugar (FBS) level was determined by samples taken early in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
43
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 24 publications
17
43
4
2
Order By: Relevance
“…12 The finding from this study was also higher than findings from a community-based study in Southern Ethiopia (1.9%), 18 institution-based study in Addis Ababa (2.6%), 19 20.90% 66.70% and Dessie town, Northeast Ethiopia (6.8%), 20 and Mizan Aman Town, Southwest Ethiopia, (6.5%). 21 The prevalence of undiagnosed diabetes in Bahir Dar city, northwest Ethiopia was 10.2%, 22 which was slightly lower than the findings of the current study whilst the current study was consistent with the study in Spain (13.8%), 6 and Tanzania (12%). 7 A community-based study in Sudan revealed the prevalence of diabetes at 18.6%, 23 which was higher than the findings of the current study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…12 The finding from this study was also higher than findings from a community-based study in Southern Ethiopia (1.9%), 18 institution-based study in Addis Ababa (2.6%), 19 20.90% 66.70% and Dessie town, Northeast Ethiopia (6.8%), 20 and Mizan Aman Town, Southwest Ethiopia, (6.5%). 21 The prevalence of undiagnosed diabetes in Bahir Dar city, northwest Ethiopia was 10.2%, 22 which was slightly lower than the findings of the current study whilst the current study was consistent with the study in Spain (13.8%), 6 and Tanzania (12%). 7 A community-based study in Sudan revealed the prevalence of diabetes at 18.6%, 23 which was higher than the findings of the current study.…”
Section: Discussionsupporting
confidence: 85%
“…19 Ever checked blood glucose level (AOR=1.91, 95% CI 1.03 to 3.51), family history of DM (AOR=2.5, 95% CI 1.21 to 5.18), do not know the symptoms of diabetes (AOR=2.06, 95% CI 1.08 to 3.89), body mass index (BMI) >25 kg/m2 (AOR=1.98, 95% CI 1.09 to 3.60) were factors associated with diabetes. 22 20 Waist circumference smoking habits, hypertension, total cholesterol level, and body mass index were factors significantly associated with diabetes. 21 Family history of diabetes, older age, and physical inactivity were significantly associated with diabetes among urban population while alcohol consumption was inversely associated with diabetes mellitus in a rural population.…”
Section: Discussionmentioning
confidence: 94%
“…This is because physical activities minimize the risk of hyperglycemia through increasing insulin-stimulated glycogen synthesis, enhancing muscle glucose uptake, making the muscle being more sensitive to the actions of insulin and it balances the average caloric intake and expenditure by the body cells. 51 Similar to the previous research reports, 28,33,37,52,53 the occurrence of unrecognized DM is higher among adults with central obesity (larger waist circumference). This might be because, in individuals with expanded abdominal fat accumulation, adipose tissue releases highly active hormones (adipokines), increased amount of free fatty acids, glycerol, pro-inflammatory cytokines, and other factors that are involved in the development of insulin resistance and impairment of glucose homeostasis.…”
Section: Discussionsupporting
confidence: 81%
“…1). Of the 23 articles reported, 11 were from Ethiopia [28][29][30][31][32][33][34][35][36][37][38], Three from Ghana [39,40], and the remaining eight studies from Sudan [41], Benin [42], Botswana [43], Egypt [44], Burkina Faso [45], Zambia [46],Tunisia [47] and South Africa [46].…”
Section: Identification and Description Of Studiesmentioning
confidence: 99%